Evaluasi Pengelolaan Emergency Trolley terhadap Pasien Gawat Darurat - Putri, Adifa Yuliana; Cholisah, Elis (Journal of Telenursing (JOTING), 2023)
This research aims to find out what the input, process and output of the Sariningsih Hospital emergency trolley are and how they are managed. The method used is qualitative using a descriptive design. The research results show that aspects of research input, process and output are explained in the discussion. Emergency room (96% appropriate; 4% not appropriate); outpatient clinics (98% appropriate; 2% not appropriate); hospital emergency department (87% appropriate; 13% not appropriate); Polyclinics (87%) and inpatients (87%) were all included in this study. Conclusion management input (input) emergency trolley has done everything necessary to complete the job. Emergency trolley management does not need to meet external content requirements, and the availability of relevant forms is in accordance with the rules. The responsible manager has followed all appropriate protocols in managing the room, including the use of emergency trolleys and the preparation and administration of medications. The person in charge of the room ensures that all output, in the form of complete documents on the emergency train, is properly managed and recorded. Keywords: Emergency Trolley, Emergency Medicine, Management